Female board members and corporate performance - Nasonenko, Angelina; Dvořáková, Zuzana, 1960-; Höschlová, Eva; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2015)
The purpose of this thesis is to investigate the relationship between female representation on boards of British FTSE 100 companies and their corporate performance. The theoretical section sets the foundation for the initial hypotheses that there is a positive relationship between the percentage of women on corporate boards and a firm's profitability, measured as ROE and ROIC. The methodological part establishes an analytical framework to test these hypotheses utilizing the so-called 'quartile approach'. The FTSE 100 companies are categorized into quartiles in accordance with their respective percentage of female directors and subsequently, the average values of ROE and ROIC are calculated for each quartile and compared between each other. The research in the practical part of the thesis shows that profitability varies significantly when comparing the least and most gender diverse FTSE 100 boards. The aim of the thesis was reached by proving the positive correlation between the percentage of female board members and profitability, validated by sensitivity and statistical analyses.
Vedoucí práce: Zuzana Dvořáková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses